The Nativity Chapel in the Church of Santa Maria dei Martiri in Maranola: Court Patronage in Southern Latium - D’Attanasio, Marco (Actual Problems of Theory and History of Art, 2021)
In Maranola there is the Church of Santa Maria dei Martiri, famous for the Nativity Chapel. Despite the fact that the sacellum was realized in modern age, it is very difficult to obtain sure information, because of the lack of documentation. The sacellum has a rectangular plan, at about half of its height it is divided horizontally by a barrel vault that simulates a cave; the two floors are connected by stairs on the left. In the cross vault of the upper level there are painted the four Evangelists with their symbols. In the lower level of the chapel are recognizable two pictorial layers in which the fragmentary Nativity is visible. It is possible to date these paintings to the beginning of the 16th century because they are stylistically close to the manner of Cristoforo Scacco, a painter well known in Southern Latium at that time. The decoration of the chapel is completed by a Nativity scene with twenty-seven terracotta sculptures. In the lower floor of the chapel there are: Baby Jesus, The Holy Virgin, St. Joseph, the ox and the donkey and two Prophets: king David and Malachi. In the upper floor there are the Three Magi, the Annunciating Angel, two shepherds and many animals. The crèche is stylistically close to the Neapolitan sculpture of the end of the 15th — beginning of the 16th century. Even if there are no documents, it seems possible to connect the patronage of the Nativity Chapel to Caterina Pignatelli, the wife of the count of Fondi Onorato II Caetani. With this patronage, she wanted to underline her power over the feud of Maranola.